Penerapan Model Demonstrasi pada Pembelajaran PAI Materi Fardhu Kifayah dalam Meningkatkan Hasil Belajar Siswa Kelas XI IPA SMAS PLUS Muhammadiyah di Subulussalam - Sarianti Sarianti; Mukhsin Nyak Umar; Yusra Jamali (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2023)
This study aims to examine the application of the demonstration model in learning Islamic Religious Education (PAI) with a focus on Fardhu Kifayah material and its impact on improving student learning outcomes in class XI Science at SMAS Plus Muhammadiyah in Subulussalam. The research method used is Classroom Action Research (CAR) with three cycles. The research data were obtained through observation, written tests, and document analysis. The demonstration model is applied in each cycle with structured steps and actively involves students in the practice of Fardhu Kifayah. The results showed a significant increase in student learning outcomes after the implementation of the demonstration model. The conclusion of this study is that the application of the demonstration model in PAI learning Fardhu Kifayah material can provide positive benefits in improving student learning outcomes. This model allows students to see and experience Fardhu Kifayah's practice firsthand, which helps increase students' understanding, skills, and motivation in carrying out the ritual.